Analisis Preferensi Risiko Petani pada Usahatani Kubis Organik di Kecamatan Baso, Kabupaten Agam, Sumatera Barat - Reny Hidayati; Anna Fariyanti; Nunung Kusnadi (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2015)
Risk preferences of farmers determine to adoption of a technology. This study aims to determine risk preferences of cabbage farmers in Baso Sub-district. Analysis of risk preferences using a model of risk preferences Kumbhakar 2002. Results show that organic cabbage farmers are risk-averse, impacting the slow adoption of organic farming.